2017
DOI: 10.5231/psy.writ.2017.19042
|View full text |Cite
|
Sign up to set email alerts
|

Radicalización ideológico-política y terrorismo: un enfoque psicosocial

Abstract: ResumenLa radicalización ideológico-política y el terrorismo generan una serie de consecuencias desastrosas para el correcto funcionamiento de una sociedad. Actualmente, situaciones de convulsión social consecuencia de la crisis económica y migratoria, así como el terrorismo de corte ideológico-religioso, están ocasionando un aumento de la polarización y la radicalización ideológico-política. El planteamiento de intervenciones preventivas eficaces para atajar estos procesos requiere de un estudio sistemático y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Radicalism has primarily been studied in contexts of terrorism (Bazaga & Tamayo, 2021;Gøtzsche-Astrup et al, 2020), mainly for religious (Gómez et al, 2022) or political (Torres-Marín et al, 2017) reasons. However, some studies have explored this phenomenon in social movements and found tendencies to radicalization in some movements, including those with ecological claims (Belli et al, 2022;Costa, 2008).…”
Section: Palabrasmentioning
confidence: 99%
See 1 more Smart Citation
“…Radicalism has primarily been studied in contexts of terrorism (Bazaga & Tamayo, 2021;Gøtzsche-Astrup et al, 2020), mainly for religious (Gómez et al, 2022) or political (Torres-Marín et al, 2017) reasons. However, some studies have explored this phenomenon in social movements and found tendencies to radicalization in some movements, including those with ecological claims (Belli et al, 2022;Costa, 2008).…”
Section: Palabrasmentioning
confidence: 99%
“…El radicalismo ha sido estudiado mayoritariamente en los contextos del terrorismo (Bazaga & Tamayo, 2021;Gøtzsche-Astrup et al, 2020), principalmente por motivos religiosos (Gómez et al, 2022) o políticos (Torres-Marín et al, 2017). No obstante, algunas investigaciones han profundizado en este fenómeno en el caso de movimientos sociales, encontrando tendencias de radicalización en algunos movimientos como el ecologista (Belli et al, 2022;Costa, 2008).…”
Section: Participación Social Y Radicalismo: El Papel Mediador De La ...unclassified
“…Other perspectives which reach a certain level of consensus are the consideration of the Salafist-jihadist matrix as the breeding ground where radicalization takes place but in combination with other factors that are usually specified in two categories: internal push factors and external pull factors (Table 1) (Mirchandani 2017). Regarding internal factors, there are existential crisis episodes, which are common to almost all the terrorists: real or perceived oppression, real or perceived exclusion, anger and frustration due to unfulfilled expectations-the higher these are, the more difficult they are to satisfy, which connects both poor and unsatisfied middle classes or rich people with a desire for recognition, to mention several apparently opposite profiles-a lack of sense, a search for ties, for belonging and bonding, and a desire for recognition and a better life (Torres-Marín et al 2017). The pull factors would consist of the appeal of the Salafist-jihadist ideology itself because in a very simple (and reductionistic) manner, it explains Muslim individual and collective marginalization and offers a direct and clear alternative based on the beauty of the group belonged to, fascination for adventure and violence, the possibility of being acknowledged, of having a life which makes sense, in the other life (if you commit suicide) or in the caliphate, etc.…”
Section: External Pull Factors and Internal Push Factorsmentioning
confidence: 99%
“…Other perspectives which reach a certain level of consensus are the consideration of the Salafist-jihadist matrix as the breeding ground where radicalizacion takes place but in combination with other factors that are usually specified in two categories: internal push factors and external pull factors (Mirchandani, 2017). Regarding internal factors, we talk about existential crisis episodes commons in almost all the terrorists, real or perceived oppression, real or perceived exclusion, anger and frustration for the unfulfilled expectations -the higher, the more difficult to satisfy, which connects both poor and middle unsatisfied classes or rich people with a desire for recognition, to mention several profiles apparently opposite-, lack of sense, search for ties, belonging and bonding, recognition and a better life desire (Trujillo et al, 2017). Pull factors would be appeal of the Salafist-jihadist ideology, because in a very simple way (and reductionistic) explains the way Muslims individual and collective marginalization and offers a direct and clear response; beauty of the belonging group, the cell; fascination for adventure and violence; possibility of being recognised, having a full of sense life in the other life (if you are a suicide) or in the caliphate, etc.…”
Section: Created By Vahid Digital Marketingmentioning
confidence: 99%